Evaluation of a Preliminary Assessment Method for Identifying the Maturity of Communication in Distributed Software Development. - Leitão Junior, Nelson G. de Sá; de Farias Junior, Ivaldir H.; Marczak, Sabrina; Santos, Rodrigo; Furtado, Felipe; de Moura, Hermano P. (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2017)
Communication is still one of the main challenges of distributed software development and it is important for distributed teams to be able to maintain effective communication, i.e., to communicate properly and in a timely manner to facilitate the management of project activities and then to contribute to the process quality. Communication is also a critical aspect for Software Reuse in global development since it affects trust and can foster the not-invented-here syndrome. In order to handle such challenge, this paper presents an evaluation of a preliminary version of an assessment method for identifying communication maturity, based on the Communication Maturity Model (C2M), a model that supports the improvement of communication processes and practices in distributed organizations. We present the preliminary assessment method definition and its evaluation results obtained during two focal group sessions with IT professionals. Findings include a positive and promising perception on the benefits of adopting this method, and a demand for further work towards its maturation.